2015
DOI: 10.1039/c5nr00799b
|View full text |Cite
|
Sign up to set email alerts
|

Dual stimuli polysaccharide nanovesicles for conjugated and physically loaded doxorubicin delivery in breast cancer cells

Abstract: The present work reports the development of pH and enzyme dual responsive polysaccharide vesicular nano-scaffolds for the administration of doxorubicin via physical loading and polymer-drug conjugation to breast cancer cells. Dextran was suitably modified with a renewable resource 3-pentadecyl phenol unit through imine and aliphatic ester chemical linkages that acted as pH and esterase enzyme stimuli, respectively. These dual responsive polysaccharide derivatives self-organized into 200 ± 10 nm diameter nano-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 54 publications
1
85
0
Order By: Relevance
“…Similar results were also observed for the reaction with cysteine (details are given in SF 9). [39][40][41] Amount of cisplatin released were monitored using OPD assay. From figures 7c, it was very clear that the free cisplatin reacted with these thiol species and produced Pt-S bond.…”
Section: Gsh Resistance and Enzyme-responsive Cleavagementioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were also observed for the reaction with cysteine (details are given in SF 9). [39][40][41] Amount of cisplatin released were monitored using OPD assay. From figures 7c, it was very clear that the free cisplatin reacted with these thiol species and produced Pt-S bond.…”
Section: Gsh Resistance and Enzyme-responsive Cleavagementioning
confidence: 99%
“…37 We and other research groups had earlier reported polysaccharide vesicles, [38][39][40] amphiphilic dendrons [41][42] and block copolymer assemblies 43 having enzyme-responsiveness for delivering anticancer drug molecules such as doxorubicin and camptothecin. 37 We and other research groups had earlier reported polysaccharide vesicles, [38][39][40] amphiphilic dendrons [41][42] and block copolymer assemblies 43 having enzyme-responsiveness for delivering anticancer drug molecules such as doxorubicin and camptothecin.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed cellular uptake studies were done earlier to quantify the fluorescent intensity of the Rh-B loaded vesicles in normal cells (wild type mouse embryonic fibroblasts, WT-MEFs), breast cancer cells (MCF-7), and colon cancer cells (DLD-1). 27 The Rh-B vesicular particles were found to be stable and they were not found to affect both normal and cancer cells even though differences exist at the microlevel in The Journal of Physical Chemistry B Article these cell types at their intracellular compartments. Thus, the significant difference in lifetime of Rh-B in free and encapsulated form can be utilized for studying the release rate from vesicles.…”
Section: ■ Introductionmentioning
confidence: 98%
“…These vesicular structures were characterized by electron microscopy, atomic force microscopy, and dynamic and static light scattering methods, and these details were reported elsewhere. 25,27 A schematic representation of DOX and Rh-B loading into vesicles (see Figure 2a) . This indicated that the steady state absorbance and emission spectroscopic methods were not able to distinguish between the free drug in solution and drug encapsulated in vesicles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dextran, chitin, chitosan and their derivatives have been investigated for their use as drug carriers. Most of the vesicles in this category are modified polysaccharides adducted with either small (trimethyl-) 141,142 or larger (3-pentadecylphenol-) 143,144 hydrophobic groups to render them amphipathic. Chitosan derived polymer vesicles are the most studied in this category.…”
Section: Structures Of Self-assembling Nanoparticlesmentioning
confidence: 99%